Procedural Justice and Police Legitimacy: A Test of Measurement and Structure - Gau, Jacinta M. (American journal of criminal justice, 2014)
The procedural justice theory of police legitimacy has received substantial empirical support, yet too little attention has been paid to the operationalization and measurement of these important theoretical constructs. In particular, it is unclear whether the items used to represent procedural justice and police legitimacy possess convergent and discriminant validity. The current study uses confirmatory factor analysis to test for the measurement properties of these constructs and expands upon prior research by also including a measure of encounter-based procedural justice in addition to a scale tapping into global beliefs. The results provide mixed support for discriminant and convergent validity between legitimacy and global procedural justice. Full structural equation models test an alternative specification of one of the popular measurement methods for legitimacy, and compare the relative impact of each type of procedural justice. The findings indicate that while specific procedural justice predicts legitimacy, global procedural justice has a stronger influence. Implications for measurement and police policy are discussed.